2018
DOI: 10.1073/pnas.1812938115
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembling supramolecular dendrimer nanosystem for PET imaging of tumors

Abstract: SignificanceNanotechnology-based imaging is expected to bring breakthroughs in cancer diagnosis by improving imaging sensitivity and specificity while reducing toxicity. Here, we developed an innovative nanosystem for positron emission tomography (PET) imaging based on a self-assembling amphiphilic dendrimer. This dendrimer assembled spontaneously into uniform supramolecular nanomicelles with abundant PET reporting units on the surface. By harnessing both dendrimeric multivalence and the “enhanced permeation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 34 publications
1
72
0
Order By: Relevance
“…While dendrimers have been explored for targeting brain tumors, relatively few studies have performed quantitative analysis of dendrimer accumulation in orthotopic brain cancer models 46‐48 . Compared to other types of dendrimers injected via tail vein in flank tumor models, our hydroxyl‐terminated PAMAM dendrimer results exhibit similar levels of tumor accumulation despite needing to overcome physical transport barriers in orthotopic brain tumors that flank tumors lack 49‐51 . Compared to other types of nanoparticles explored in orthotopic brain tumors, G6 shows a ~100‐fold greater in tumor accumulation than liposomal 52 nanoparticles and ~10‐fold greater than G4 and reported tumor levels of gold 53,54 and PEGylated iron oxide 55 nanoparticles.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…While dendrimers have been explored for targeting brain tumors, relatively few studies have performed quantitative analysis of dendrimer accumulation in orthotopic brain cancer models 46‐48 . Compared to other types of dendrimers injected via tail vein in flank tumor models, our hydroxyl‐terminated PAMAM dendrimer results exhibit similar levels of tumor accumulation despite needing to overcome physical transport barriers in orthotopic brain tumors that flank tumors lack 49‐51 . Compared to other types of nanoparticles explored in orthotopic brain tumors, G6 shows a ~100‐fold greater in tumor accumulation than liposomal 52 nanoparticles and ~10‐fold greater than G4 and reported tumor levels of gold 53,54 and PEGylated iron oxide 55 nanoparticles.…”
Section: Discussionmentioning
confidence: 93%
“…This is in contrast to free drug administration of chemotherapies, which quickly clear from tumor tissue while accumulating in the liver at much greater concentrations 60,76 . These PAMAM dendrimers also compare favorably to gold nanoparticles, PEGylated iron oxide nanoparticles, and other classes of dendrimers, which exhibit slightly higher kidney levels but a significantly greater liver accumulation of 2–70% of the initial dose retained 49,50,54,55,77 . Taken together with their tumor accumulation results, this biodistribution profile indicates that these dendrimers may yield a large therapeutic window for effective and safe treatments for brain cancers.…”
Section: Discussionmentioning
confidence: 95%
“…Nanomaterials (NM) are structures with dimensions of no more than 100 nm, used as excipients that can be important in the solving of the bioavailability of active substances issues [ 217 , 218 , 219 , 220 ].…”
Section: Biomedical Applications Of Dendrimersmentioning
confidence: 99%
“…Nanotechnology-based imaging is a promising field of interest for overcoming some limitations to the use of imaging agents, and especially for enhancing permeation and retention (EPR), because of the possibility of improving the specificity and the sensitivity of imaging [ 220 ].…”
Section: Biomedical Applications Of Dendrimersmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32][33][34][35] Photoacoustic imaging (PAI), which convert incident light into acoustic waves by exciting nanoparticle or chromophore with a strong optical absorbance spectrum in the NIR region, show powerful advantage such as deep tissue penetration, high spatial resolution, high signal-noise ratio in contrast to conventional X-ray computed tomography (CT), positron emission tomography (PET), magnetic resonance imaging (MRI) and uorescence images (FLI). [36][37][38][39][40][41][42][43][44][45][46][47][48][49] In this work, we report a biocompatible PVP-coated Sb 2 Se 3 nanorods as PTT theranostic agents with relatively narrow band gap energy, which are responsive to the light (808 and 980 nm) in the NIR-I bio-windows (Scheme 1). The PTT studies in vitro and in vivo showed that PVP-coated Sb 2 Se 3 nanorods were effective for photoacoustic imaging and photothermal destruction of cancer cell.…”
Section: Introductionmentioning
confidence: 99%